Carbon footprints by stage of chronic kidney disease: The case of Japan - Kei Nagai; Sho Hata; Norihiro Itsubo; Kunitoshi Iseki; Kunihiro Yamagata; Keisuke Nansai (Elsevier, 2024)
Introduction: The nexus between carbon footprints and chronic kidney disease (CKD) progression have not been clarified, so it has not been possible to examine the prevention of disease severity as a potential countermeasure for decarbonization. Material and methods: The study included 70,627 subjects aged 40-74 years and diagnosed with CKD stage by specific health checkups in 2014-2015. Greenhouse gas (GHG) emissions in Japan were formulated with the 2015 environmental input-output model. The carbon footprints by CKD stage were calculated with annual treatment cost according to renal function indicators, namely estimated glomerular filtration rate (eGFR) and proteinuria. Results: The annual carbon footprint per patient with induction of dialysis due to CKD was estimated to be 3.9 tCO2e, in contrast to 0.31 tCO2e in subjects without dialysis. Highlighting the relationship between the carbon footprint and the slope of eGFR as the CKD stage advances, the carbon footprint of care for patients with a stable eGFR in CKD stage G2 or better was 300 kgCO2e in males and 280 kgCO2e in females. Yet, in CKD stages G3a and G3b or worse, the carbon footprint for a rapid decrease in eGFR (30 % or greater per year) was 620 kgCO2e and 1440 kgCO2e in males and 430 kgCO2e and 1270 kgCO2e in females, respectively. Conclusion: Effective interventional treatments to prevent disease severity in CKD contribute to both the health of the patient and the mitigation of GHG emissions.